1971
DOI: 10.1159/000121980
|View full text |Cite
|
Sign up to set email alerts
|

Neurohypophysial Hormones in the Pars Nervosa of the Mouse with Hereditary Nephrogenic Diabetes Insipidus

Abstract: Vasopressor and oxytocic activities were detectable in the pars nervosa of mice with hereditary diabetes insipidus (DI Os/+ strain). This finding shows that the diabetes insipidus of DI mice is due to a primary defect of the kidney and not to vasopressin deficiency. Both activities of the DI mice were significantly higher than in normal mice (VII +/+) when the activities were expressed in terms of the individual. However, when the activity was expressed per mg of dry weight of the pars nervosa, the difference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
1

Year Published

1972
1972
1992
1992

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 3 publications
2
4
1
Order By: Relevance
“…Similarly, Stewart Sc Stewart (1969), have bioassayed the neurohypophysial hormones of DI +/+ and DI Os/ + mice and irrespective of groups, their activity is equivalent to 140-200 mU for vasopressin and 80-120 mU for oxytocin. As these results are for DI Os/ + and DI +/+ combined, we cannot compare these results to our earlier results (Naik Sc Kobayashi 1971), nor the present ones. However, we can conclude from the results of Stewart 8c Stewart (1969) that these values are higher than those of VII +/+ and VII Os/+ mice.…”
Section: Resultscontrasting
confidence: 98%
See 4 more Smart Citations
“…Similarly, Stewart Sc Stewart (1969), have bioassayed the neurohypophysial hormones of DI +/+ and DI Os/ + mice and irrespective of groups, their activity is equivalent to 140-200 mU for vasopressin and 80-120 mU for oxytocin. As these results are for DI Os/ + and DI +/+ combined, we cannot compare these results to our earlier results (Naik Sc Kobayashi 1971), nor the present ones. However, we can conclude from the results of Stewart 8c Stewart (1969) that these values are higher than those of VII +/+ and VII Os/+ mice.…”
Section: Resultscontrasting
confidence: 98%
“…The present results and the evidences of others (Naik 8c Valtin 1969;Naik Sc Kobayashi 1971;Stewart Sc Stewart 1969), therefore suggest very strongly that the diabetes insipidus in the 3 genotypes of DI mice, unlike the familial diabetes insipidus in the Brattleboro rats {Valtin 1967) is not due to a failure in the synthesis of ADH. Also, Naik Sc Valtin (1969) showed that the DI mice do not suffer from primary polydipsia as do STR/N mice described by Silverstein et al (1961).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations